A new risk strategy for European cooperative banks in contemporary economic crisis - Constantinescu, Liliana-Aurora; Constantinescu, Adrian; Dumitrescu, Alexandra-Cristina (The International Conference "The European Integration - Realities and Perspectives", 2012)
The quality of the banking management and of the risk management represents the essential steps for the insurance, the security and the stability of each bank individually. In this article, the authors intends to underline the main aspects regarding the risk in sustainable development of European credit institutions and the theoretical and practical aspects that can contribute to increasing performance management in credit institutions. In times of crisis, risk management in the banking system has a greater importance than in the normal economic times. The 2011 was a year in which Romania has been hit by the repercussions of the international economic crisis.